2020
DOI: 10.3390/jcm9040943
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Intra-Articular Glenohumeral Lesions in Fractures of the Scapula Body

Abstract: Background: Scapula body fractures are rare injuries with an incidence of 1% of all fractures accounting for 3% to 5% of all upper extremity fractures. Fractures of the scapula commonly result from high-energetic trauma and fall from great height. While several studies focused on concomitant injuries of chest and head as well as the cervical spine, up to now in the common literature, no study exists analyzing the prevalence of concomitant intra-articular glenohumeral injury following extra-articular scapular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…There are studies in the literature that show significantly varied results in this regard. [1,6,[16][17][18] Interestingly, the only finding in our study that did not overlap with the literature was the absence of brachial plexus and vascular injury in any of our cases. [7,13,16] Our region is a geographically scattered rural settlement.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…There are studies in the literature that show significantly varied results in this regard. [1,6,[16][17][18] Interestingly, the only finding in our study that did not overlap with the literature was the absence of brachial plexus and vascular injury in any of our cases. [7,13,16] Our region is a geographically scattered rural settlement.…”
Section: Discussionsupporting
confidence: 58%
“…In the previous studies, rib fractures were also found to be associated with SF. [6,13,14] To the best of our knowledge, no similar study was found that revealed a statistically significant correlation between the increased number of rib fractures and SF. We think that these significantly higher rates of rib fractures are due to the difference in both the trauma mechanism and the average age.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations